Pemikiran Mohammad Hatta tentang Prinsip-Prinsip Demokrasi dan Kewarganegaraan di Indonesia - Rahmi, Gusti; Moeis, Isnarmi; Rafni, Al; Hasrul, Hasrul (Jurusan Ilmu Sosial Politik, Fakultas Ilmu Sosial, Universitas Negeri Padang, 2025)
This study aims to examine Mohammad Hatta's philosophical perspectives on the principles of democracy and citizenship in Indonesia, as articulated in his seminal work, Demokrasi Kita. The research underscores that the concept of citizenship in Indonesia should be rooted in the principles of inclusive, equitable, and participatory democracy, reflecting Hatta's visionary ideals. According to Hatta, citizens are not merely passive beneficiaries but active participants responsible for fostering a democratic and socially just society. Employing a qualitative methodology with content analysis, this study focuses on Demokrasi Kita as the primary data source, supplemented by secondary literature addressing Indonesian democracy and Hatta's contributions. The unit of analysis comprises paragraphs from the primary source that elucidate the principles of Indonesian democracy. Data validity is ensured through theoretical triangulation. The findings reveal that Hatta's conceptualization of democracy and citizenship demonstrates profound theoretical depth and remains highly relevant in contemporary contexts. While his ideas are normative in nature, they serve as a critical framework for guiding democratic practices in Indonesia today.